Altruism to Strangers for our Own Sake: Domestic Effects from Immigration - Annie Tubadji; Peter Nijkamp (Tinbergen Institute, 2012)
This paper seeks to identify relationships between human capital and cultural capital, in the context of local labour market productivity. The key constituents of human capital, identified in the literature, are jointly examined in a close-to-reality-model. The main advantage of our model of productivity is that, in addition to accounting for the filigree composition of human capital, it also takes into consideration the cultural capital present in a locality. In this manner, we are able to examine the interaction between the quality of the incoming human capital and the cultural encounter context (generating the cultural milieu effect) of the modern diverse city. To this end, we operationalize one model with data on the 'melting pot' of EU15, at NUTS2 level. The sources of our data are the Eurostat Regional Database and the World Value Survey, which have served to construct both a cross-section for the year 2001. These datasets allows us: (1) to exa mine the different groups of migrating and local human capital, their interaction and joint impact on local productivity, and (2) to cross-check for the causality direction behind our model. Our findings suggest that benefits from immigrants differ, not only due to their human capital, but also due to their culturally biased different bargaining power on the labour market.
urn:NBN:nl:ui:31-1871/38501
Keywords: Z10; O31; O43; R11; 330; human capital; cultural capital; diversity; productivity; growth; Weber; Einwanderung; Humankapital; Altruismus; Bevölkerungsstruktur; Arbeitsproduktivität; Vergleich; EU-Staaten